The IbMYB52/IbARF11L-IbDRM1 module negatively regulates the root development of sweetpotato - Li, Chengyang (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.